(untitled) (International Journal of Engineering and Computer Science, 2025)
This review article examines the potential benefits of implementing a Quality Management System (QMS) based on the requirements of the international ISO 9001 standard within gaming industry companies. The article explores the core principles and structure of an ISO 9001 QMS in the context of game development. It describes the main stages of QMS implementation in gaming companies and highlights the role of the ISO/IEC/IEEE 90003 standard in this process. Particular attention is paid to analyzing the feasibility of applying the ISO 9001 standard in the gaming industry, supported by research on the standard’s compatibility with popular development methodologies used in high-tech and creative companies, as well as real-world examples of successful implementation and certification of gaming companies under the ISO 9001 standard.